استخدام التخطيط الشبكي CPMو PERTفي جدولة عمليات الصيانة لمعمل درفلة الحديد (دراسة حالة مصنع حميشو للمعادن) - حاتم محمودي; أيمن يوسف; تركان حمزه (Tishreen University, 2019)
The research aims to study the impact of production management on industrial facilities by scheduling special production processes for the iron mill malfunction. To achieve this goal، cpm(Critical Path Method) and pert (Program Evaluating and Review Technique) were used to network planning methods in schedule maintenance operations by splitting faults into a range of activities and examining sequential relationships between them in order to achieve the time target of failures، reducing time within the limits of physical and human resources. The production processes are programmed by using the MS-PROJECT program to draw the network diagrams through the Gantt chart، show the relationships between the different activities and show the critical path depending on the time periods entered for each activity، as well as the fault pressure to reach the optimal solution، on the one hand، and fixed and variable costs on the other hand by using Excel Solver after determining the target and network constraints. The program provides the optimal solution by provides the sensitivity report of the mathematical model.   يهدف البحث إلى دراسة أثر إدارة الإنتاج على الكفاءة الإنتاجية في المنشآت الصناعية عن طريق جدولة العمليات الإنتاجية الخاصة بأعطال معمل درفلة الحديد، ولتحقيق هذا الهدف تم استخدام أساليب التخطيط الشبكي CPM(Critical Path Method) وPERT (Program Evaluating and Review Technique) في جدولة عمليات الصيانة عن طريق تقسيم الأعطال إلى مجموعة من النشاطات ودراسة العلاقات التتابعية فيما بينها بغية تحقيق الهدف الزمني للأعطال أي تخفيض الزمن ضمن حدود الموارد المادية والبشرية. ويتم برمجة العمليات الإنتاجية عن طريق استخدام برنامج MS-Project 2013 لرسم المخططات الشبكية عن طريق مخطط غانت وإظهار العلاقات بين النشاطات المختلفة وإظهار المسار الحرج اعتماداً على الفترات الزمنية المدخلة لكل نشاط، بالإضافة إلى ضغط الأعطال للوصول إلى الحل الأمثل والذي يتمثل في إحداث توازن بين زمن تنفيذ المشروع من ناحية وكل من التكاليف الثابتة والمتغيرة من ناحية أخرى عن طريق استخدام برنامج Excel Solver بعد تحديد التابع الهدف وقيود الشبكة حيث يقوم البرنامج بإعطاء الحل الأمثل عن طريق التزويد بتقرير حساسية النموذج الرياضي.